The Procrustean Bed: A History of the Arrangement of the Al Purdy Fonds - Heil, Jeremy M. (Archivaria, 2013)
In 1969, Queen’s University in Kingston, Ontario, purchased the first set of papers from Al Purdy, one of Canada’s foremost literary figures of the twentieth century. Over five decades and eleven accruals, a number of archivists have left their signature on the organization of these papers. This varied influence on the arrangement of the fonds has resulted in a scattered sequence of incompatible series. This case study examines the factors that influenced the practical application of arrangement theories in one institution, Queen’s University Archives, from the perspective of an archivist having to navigate different contexts of arrangement throughout the acquisition history of the fonds. Through interviews with the donor and with former archivists, who had arranged specific accruals to the Al Purdy Fonds, as well as through research into the institutional practices and training of Queen’s University archivists, the article examines the milieu in which series and sub-series expanded and were altered within one fonds. The article also examines how traditions of arrangement are created and propagated over time, and how the misguided pursuit of “original order” over an entire fonds can perpetuate false constructs. RÉSUMÉ  En 1969, l’Université Queen’s à Kingston, en Ontario, fit l’achat d’un premier ensemble de documents d’Al Purdy, l’une des figures littéraires canadiennes les plus importantes du vingtième siècle. Au cours des cinq décennies et onze versements qui ont suivi, un nombre d’archivistes ont laissé leur marque sur l’organisation de ces documents. Le résultat de cette influence variée sur le classement de ce fonds d’archives est une suite dispersée de séries incompatibles. Cette étude de cas examine les facteurs qui ont influencé l’application pratique des théories sur le classement dans une institution, les archives de l’Université Queen’s, à partir de la perspective d’un archiviste qui doit naviguer à travers les différents contextes de classement au cours de l’histoire de l’acquisition de ce fonds d’archives. À partir des entrevues avec le donateur et avec d’anciens archivistes qui ont organisé des versements spécifiques au fonds Al Purdy, et aussi à partir d’une recherche sur les pratiques institutionnelles et la formation des archivistes de l’Université Queen’s, cet article examine le milieu dans lequel les séries et sous-séries d’un fonds d’archives se sont étendues et ont été modifiées. Cet article examine aussi comment des traditions de classement sont crées et perpétuées avec le temps, et comment la poursuite peu judicieuse de « l’ordre d’origine » pour un fonds peut perpétuer des constructions hypothétiques erronées.